Sarcopromusca pruna (Diptera: Muscidae): phoretic for Dermatobia hominis (Diptera: Cuterebridae) eggs in Colombia - Cardona Zuluaga, Edison A (Revista Colombiana de Ciencias Pecuarias, 2012)
Summary Objective: the finding of Sarcopromusca pruna as a phoretic for Dermatobia hominis eggs is described here. The later is a frequent cattle ectoparasite (human botfly) known as nuche" in Colombia. Methods: the phoretic flies were captured in a village at San Rafael municipality (Antioquia) using Malaise-type traps installed during the months of June to August, 2004. Each Sarcopromusca specimen carried a minimum of 19 and, in some cases, up to 23 eggs of D. hominis on the right or left side of the abdominal region. Results and conclusion: this is a new report of Sarcopromusca pruna behaving as a phoretic fly for Dermatobia hominis eggs observed in Colombia. Key words: Dermatobia hominis, "human botfly", Muscidae, Oestridae, phoretic insects, Sarcopromusca pruna. Resumen Objetivo: se describe el hallazgo de Sarcopromusca pruna (S. pruna) como forético de huevos Dermatobia hominis (D. hominis) ectoparásito comúnmente conocido en Colombia como "nuche". Método: las moscas foréticas fueron capturadas en una vereda del municipio de San Rafael (Antioquia) usando trampas de intercepción tipo Malaise instaladas durante los meses de junio a agosto de 2004. Cada espécimen de Sarcopromusca transportaba un número mínimo de 19 y en algunos casos hasta 23 huevos de D. hominis en el lado derecho o en el izquierdo de la región abdominal. Resultados y conclusión: este es un nuevo reporte de S. pruna como forético de huevos de Dermatobia hominis en Colombia. Palabras clave: Dermatobia hominis, insectos foréticos, Muscidae, Nuche, Oestridae, Sarcopromusca pruna. Resumo Objetivo: relatamos a descoberta de Sarcopromusca pruna (S. pruna) como forético dos ovos de Dermatobia hominis (D. hominis), ectoparasita comumente conhecido na Colômbia como "nuche" e no Brasil como "mosca-varejeira". Métodos: as moscas foréticas foram capturadas no município de San Rafael (Antioquia), utilizando armadilhas de intercepção tipo Malaise instaladas durante os meses de junho a agosto de 2004. Cada espécimen Sarcopromusca carregava entre 19 e 23 ovos de D. hominis no lado direito ou esquerdo da região abdominal. Resultados y conclusões: este é um novo reporte da S. pruna como forético de ovos de Dermatobia hominis na Colômbia. Palavras chave: insetos foréticos, Oestridae, parasita.